Transformation of SME Business Models Through Innovation: The Case of Home Business Camp (HBC) in the Post Covid-19 Pandemic Period - Saputro, Budi Purnomo; Kusmantini, Tititk; Utami, Yekti; Adiyatna, Hafidh Rifky; Hadyantari, Faizatu Almas (Westscience Press, 2024)
Through analysis that, you can concluded that market orientation, orientation entrepreneurship, business model innovation, and performance development product new each other related in SME context. Strong market and entrepreneurial orientation can push business model innovation, which in turn can increase performance development product new. Business model innovation is also possible role as an internal mediator connection between market orientation, orientation entrepreneurship, and performance development product new. Therefore​ that's important for SMEs to Keep going do transformation business through innovation To use survive and compete in a competitive market, especially during the COVID-19 pandemic.